Comparing the Role of ROS and RNS in the Thermal Stress Response of Two Cnidarian Models, Exaiptasia diaphana and Galaxea fascicularis - Talisa Doering; Justin Maire; Wing Yan Chan; Alexis Perez-Gonzalez; Luka Meyers; Rumi Sakamoto; Isini Buthgamuwa; Linda L. Blackall; Madeleine J. H. van Oppen (MDPI AG, 2023)
Coral reefs are threatened by climate change, because it causes increasingly frequent and severe summer heatwaves, resulting in mass coral bleaching and mortality. Coral bleaching is believed to be driven by an excess production of reactive oxygen (ROS) and nitrogen species (RNS), yet their relative roles during thermal stress remain understudied. Here, we measured ROS and RNS net production, as well as activities of key enzymes involved in ROS scavenging (superoxide dismutase and catalase) and RNS synthesis (nitric oxide synthase) and linked these metrics to physiological measurements of cnidarian holobiont health during thermal stress. We did this for both an established cnidarian model, the sea anemone Exaiptasia diaphana, and an emerging scleractinian model, the coral Galaxea fascicularis, both from the Great Barrier Reef (GBR). Increased ROS production was observed during thermal stress in both species, but it was more apparent in G. fascicularis, which also showed higher levels of physiological stress. RNS did not change in thermally stressed G. fascicularis and decreased in E. diaphana. Our findings in combination with variable ROS levels in previous studies on GBR-sourced E. diaphana suggest G. fascicularis is a more suitable model to study the cellular mechanisms of coral bleaching.